(untitled) (Proceeding of the International Conference on Arts and Humanities, 2018)
In this paper, I underline the similarities between historical art strategies, represented by Land Art, Povera and Performance Art, and those applied today by artists working with video-game technology. The former were art movements interested in the immediate experience of our surrounding reality. They overflowed the boundaries of the conventions of art by taking over the physical presence of space, objects and our bodies as their medium for work: they proposed aesthetic experiences that questioned the “cultural layer” we interpose between our senses and nature. A generation of artists working with videogames also claim some immediate experience: one from the intangible domains of the digital. They embrace another “cultural layer”, one that necessarily interposes between us and the intangible nature of the digital. That layer is the User Interface, a technology that allows us to operate the new media by means of metaphors of our familiar nature: space, time, objects, beings and physical phenomena. The interface of a video game represents a “habitable” blend of our physical experience with the fantastic possibilities of the digital: we can feel it and intervene in it, embodied in avatars. The artistic proposals and interventions inside video games warn and inform us about the hybrid context of the digital.